Special report on the consensus QIBA profile for objective analytical validation of non-calcified and high-risk plaque and other biomarkers using computed tomography angiography - Buckler, Andrew J.; Abbara, Suhny; Budoff, Matthew J.; Carr, John Jeffrey; De Cecco, Carlo N.; DeMarco, J. Kevin; Ferencik, Maros; Figtree, Gemma A.; Ikuta, Ichiro; Kolossváry, Márton; Konrad, Mathis; Lal, Brajesh K.; et al. (Academic radiology, 2024)
Rationale and Objectives - Evidence is building in support of the clinical utility of atherosclerotic plaque imaging by computed tomography angiography (CTA). There is increasing organized activity to embrace non-calcified plaque (NCP) as a formally defined biomarker for clinical trials, and high-risk plaque (HRP) for clinical care, as the most relevant measures for the field to advance and worthy of community efforts to validate. Yet the ability to assess the quantitative performance of any given specific solution to make these measurements or classifications is not available. Vendors use differing definitions, assessment metrics, and validation data sets to describe their offerings without clinician users having the capability to make objective assessments of accuracy and precision and how this affects diagnostic confidence. - Materials and Methods - The QIBA Profile for Atherosclerosis Biomarkers by CTA was created by the Quantitative Imaging Biomarkers Alliance (QIBA) to improve objectivity and decrease the variability of noninvasive plaque phenotyping. The Profile provides claims on the accuracy and precision of plaque measures individually and when combined. - Results - Individual plaque morphology measurements are evaluated in terms of bias (accuracy), slope (consistency of the bias across the measurement range, needed for measurements of change), and variability. The multiparametric plaque stability phenotype is evaluated in terms of agreement with expert pathologists. The Profile is intended for a broad audience, including those engaged in discovery science, clinical trials, and patient care. - Conclusion - This report provides a rationale and overview of the Profile claims and how to comply with the Profile in research and clinical practice. - Summary Statement - This article summarizes objective means to validate the analytical performance of non-calcified plaque (NCP), other emerging plaque morphology measurements, and multiparametric histology-defined high-risk plaque (HRP), as outlined in the QIBA Profile for Atherosclerosis Biomarkers by CTA.
Online verfügbar: 26. Juli 2024, Artikelversion: 26. November 2024
Gesehen am 04.08.2025